Enhanced ozone loss by active inorganic bromine chemistry in the tropical troposphere. (April 2017) - Le Breton, Michael; Bannan, Thomas J.; Shallcross, Dudley E.; Khan, M. Anwar; Evans, Mathew J.; Lee, James; Lidster, Richard; Andrews, Stephen; Carpenter, Lucy J.; Schmidt, Johan; Jacob, Daniel; Harris, Neil R.P.; et al.
Abstract: Bromine chemistry, particularly in the tropics, has been suggested to play an important role in tropospheric ozone loss although a lack of measurements of active bromine species impedes a quantitative understanding of its impacts. Recent modelling and measurements of bromine monoxide (BrO) by Wang et al. (2015) have shown current models under predict BrO concentrations over the Pacific Ocean and allude to a missing source of BrO. Here, we present the first simultaneous aircraft measurements of atmospheric bromine monoxide, BrO (a radical that along with atomic Br catalytically destroys ozone) and the inorganic Br precursor compounds HOBr, BrCl and Br2 over the Western Pacific Ocean from 0.5 to 7 km. The presence of 0.17–1.64 pptv BrO and 3.6–8 pptv total inorganic Br from these four species throughout the troposphere causes 10–20% of total ozone loss, and confirms the importance of bromine chemistry in the tropical troposphere; contributing to a 6 ppb decrease in ozone levels due to halogen chemistry. Observations are compared with a global chemical transport model and find that the observed high levels of BrO, BrCl and HOBr can be reconciled by active multiphase oxidation of halide (Br − and Cl − ) by HOBr and ozone in cloud droplets and aerosols. Measurements indicate that 99% of the instantaneous free Br in the troposphere up to 8 km originates from inorganic halogen photolysis rather than from photolysis of organobromine species. Highlights: We present results from simultaneous airborne measurements of a number of gaseous inorganic bromine species in the tropics. BrO, HOBr, BrCl and Br2 represent 99% of the free Br, contrary to current theory. New multi phase chemistry scheme into GEOS Chem reveals the underestimation of halogen chemistry within standard models. Inorganic bromine species can contribute up to 6 ppb O3 loss in the tropical troposphere, 20% of the total O3 destruction.